A chronotopic approach to identity performance in a Facebook meme page. (October 2018) - Procházka, Ondřej
Highlights: Identity work on Facebook is viewed as organized and ordered by specific chronotopic (timespace) conditions. Memes appear in certain chronotopic conditions which in turn provide affordances and constraints for communicative practices. Perceived or possible transgressions against chronotopic conditions are managed by 'vigilantes' through interaction. The management of transgressions testifies to the tentative character of normative frameworks. Abstract: This paper focuses on the negotiation of normativity in Facebook pages that create, share and react to multimodal cultural artefacts generally known as internet memes. Attention is paid to performances of 'vigilante' identity – reactions in comment sections to perceived or possible transgressions against normative orders of the community. It is assumed that normative negotiations largely depend on characteristics of internet memes that are also shaped by their trajectories of usage in various environments, and hence also by their history. Identity work is thus approached as a chronotopically organized phenomenon; memes appear in certain chronotopic (timespace) configurations which ratify certain communicative practices and the way people orient to them in discussion. Seeing much of the identity work as chronotopically organized and dialogically negotiated opens up the path to a greater degree of complexity in analysis and brings new insights for the study of identity in social media.